Community-Centered School Leadership: Radical Care and During COVID-19 - Leticia Alvarez Gutiérrez; Taeyeon Kim; Sonny Partola; Paul J. Kuttner; Amadou Niang; Alma Yanagui; Laura Hernández; Gerardo R. López; Jennifer Mayer-Glenn (SAGE Publishing, 2022)
We share school leaders' perspectives on Zoom videos concerning the needs of immigrant and refugee families in Title I schools. In these videos, participants crafted and shared personal narratives about their leadership experiences during the COVID-19 era of education. Rooted in participatory design research methods, the process of designing these videos were both a research project and an intervention to assist families and school leaders to better understand each other. We present a close analysis of administrators' perspectives and describe how our codesigned video methodology enabled participants to coconstruct new meanings of school-community relationships during the pandemic through a radical care framework. We conceptualize these reimaginings as aperturas-cracks in the dominant family engagement paradigm that allow us to collectively work towards transformative ends which we term community-centered school leadership. We conclude the article with recommendations for how both school leadership and research can approach and reimagine family engagement postpandemic.